Improved Design of Uniform SIW Leaky Wave Antenna With Suppression of Unwanted Mode - Amin Mahmoodi Malekshah (IEEE, 2021)
In this paper, periodic perturbations are employed on the broad wall of a substrate integrated waveguide (SIW) long slot leaky-wave antenna (LWA) to eliminate the excited unwanted mode. The presence of unwanted mode in the uniform LWA is identified by using the amplitude and phase of the electric field at the slot. Using the electric field data in the structure, propagation constants and amplitudes of desired and unwanted modes are obtained. In order to preserve the desired leaky mode and suppress the unwanted mode, periodic transverse slots are added to one side of the uniform longitudinal slot. Suppressing unwanted mode results in good consistency between the desired and designed radiation characteristics. Comparison between two LWA designs, with and without suppressing unwanted mode, for achieving −25 dB sidelobe level (SLL) and beam direction of 40° at 17 GHz, demonstrates high accuracy of the proposed design procedure. A prototype of the modified antenna is fabricated, and measured results are presented at 16, 17, and 18 GHz for validation.